Thermochemical heat storage material and preparation method thereof

By adding thermal reinforcement to the inorganic hydroxide-based heat storage material and combining other auxiliary agents, the problem of low thermal conductivity of the material is solved, efficient thermal energy storage and release is achieved, and the thermal conductivity and energy storage efficiency of the material is significantly improved.

CN119505831APending Publication Date: 2025-02-25CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534431.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The thermal conductivity of existing inorganic hydroxide-based heat storage materials is low, which affects the efficiency of heat storage and exothermic performance of heat storage equipment.

Method used

By adding thermally conductive enhancers such as graphite, silicon carbide, aluminum nitride, alumina, etc. to the inorganic hydroxide-based heat storage material, and combining surfactants, thickeners and emulsifiers, specific mixing and treatment methods are adopted to improve the thermal conductivity of the material.

Benefits of technology

The thermal conductivity coefficient of thermochemical heat storage materials has been significantly improved, reaching 1.099W/(m·K), an increase of 43.5%, while reducing energy loss and improving energy storage density and temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505831A_ABST
    Figure CN119505831A_ABST
Patent Text Reader

Abstract

The thermochemical heat storage material comprises the following raw material components in parts by mass: 250-99 parts of Ca (OH), 1-50 parts of a heat conduction enhancer, 1-6 parts of a surfactant, 1-3 parts of a thickening agent and 4-6 parts of an emulsifier. According to the preparation method of the thermochemical heat storage material, the ratio of Ca (OH) 2 to the heat conduction enhancer is (50-99): (1-50), the heat conductivity coefficient of the thermochemical heat storage material is in a rising trend along with change of the proportion of the heat conduction enhancer, and linear adjustment of the heat conductivity coefficient can be achieved by changing the mass ratio of Ca (OH) 2 to the heat conduction enhancer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical energy storage, and specifically relates to a thermochemical heat storage material and a preparation method thereof. Background Art

[0002] The demand for renewable energy such as wind and solar energy in new power systems has gradually occupied an important position. The instability of energy, long-term storage of energy and efficient conversion are the key issues for the effective use of new energy. Efficient, stable and low-cost heat storage technology is the basis for the effective use of new energy. According to the different energy storage principles, heat storage systems are divided into three types: sensible heat, latent heat and thermochemical heat storage. Among them, the thermochemical energy storage system uses reversible chemical reactions to store and release energy through the breaking and recombination of chemical bonds. Compared with other methods, it has a greater energy storage density and a wider energy storage temperature range, and the energy loss is small. It can realize seasonal energy storage without special insulation measures.

[0003] The current typical thermochemical energy storage system can be divided into metal hydride system, metal oxide system, organic system, inorganic hydroxide system, ammonia decomposition system, carbonate system, etc. according to the different reactants. Among them, the inorganic hydroxide system has the advantages of a wide operating temperature range, non-corrosive products, and environmental friendliness, and has a very broad application prospect. However, as the key medium of heat storage technology, the thermal conductivity of inorganic hydroxide-based heat storage materials is low, which not only affects the efficiency of heat storage and release, but also limits the performance of heat storage equipment to a certain extent, restricting the development and promotion of this material system.

[0004] Therefore, how to improve the thermal conductivity of inorganic hydroxide-based thermal storage materials is an urgent problem to be solved in the field of chemical energy storage. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of low thermal conductivity of inorganic hydroxide-based heat storage materials in the prior art, and to provide a thermochemical heat storage material and a preparation method thereof.

[0006] The purpose of the present invention is to adopt the following technical solutions to achieve:

[0007] A thermochemical heat storage material comprises: the raw materials of the material include the following components in parts by mass: 50-99 parts of Ca(OH)2, 1-50 parts of thermal conductivity enhancer, 1-6 parts of surfactant, 1-3 parts of thickener, and 4-6 parts of emulsifier.

[0008] Furthermore, the particle size of the Ca(OH)2 is 30 to 75 μm, and the particle size of the thermal conductivity enhancer is 0.1 to 60 μm.

[0009] Furthermore, the thermal conductivity enhancer is at least one of graphite, silicon carbide, aluminum nitride, aluminum oxide and titanium oxide.

[0010] Furthermore, the surfactant is at least one of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, hexadecyldimethylethylammonium bromide, hexadecyltrimethylammonium chloride and sodium polyoxyethylene fatty alcohol sulfate.

[0011] Furthermore, the thickener is at least one of polyacrylamide and polyvinyl alcohol.

[0012] Furthermore, the emulsifier is at least one of polyethylene glycol and propylene glycol.

[0013] Any of the above methods for preparing thermochemical heat storage materials comprises the following steps:

[0014] Mixing Ca(OH)2, a thermal conductivity enhancer, a surfactant, a thickener, and an emulsifier to obtain a first intermediate;

[0015] Dissolving the first intermediate in 35 to 50 parts of deionized water, stirring for 1 to 3 hours to obtain a second intermediate;

[0016] The second intermediate is filtered and placed in a vacuum drying oven for drying to obtain a precursor a;

[0017] The precursor a and the lubricant are placed in a planetary ball mill for ball milling for 0.5 to 2 hours, and then calcined at high temperature to obtain the precursor b;

[0018] The precursor b is placed in an inert gas atmosphere to fully react with water vapor to obtain the thermochemical heat storage material.

[0019] Furthermore, the lubricant is selected from organic lubricants, and the organic lubricant is selected from ethanol.

[0020] Furthermore, when the first intermediate is stirred with deionized water, the stirring temperature is 20 to 30° C. and the stirring time is 1 to 3 hours.

[0021] Furthermore, the molar ratio of the Ca(OH)2 to the lubricant is 1:0.5 to 1:5.

[0022] Furthermore, the inert gas is at least one of nitrogen or argon.

[0023] Furthermore, the drying temperature of the vacuum drying oven is controlled at 80-120° C., and the drying time is 11-13 hours.

[0024] Furthermore, the calcination temperature during the high temperature calcination is 500-1000° C., and the calcination time is 1-2 hours.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] A thermochemical heat storage material comprises: the raw materials of the material include the following components in parts by mass: 50-99 parts of Ca(OH)2, 1-50 parts of thermal conductivity enhancer, 1-6 parts of surfactant, 1-3 parts of thickener, and 4-6 parts of emulsifier. Through the above-mentioned proportion design, a thermochemical heat storage material with both high heat storage density and good thermal conductivity can be prepared to meet the needs of efficient thermal energy storage and release. In the method for preparing the thermochemical heat storage material provided by the present invention, the ratio of Ca(OH)2 and thermal conductivity enhancer is (50-99): (1-50). As the proportion of thermal conductivity enhancer changes, the thermal conductivity of the thermochemical heat storage material shows an upward trend. By changing the mass ratio of Ca(OH)2 and thermal conductivity enhancer, linear regulation of thermal conductivity can be achieved. The synergistic effect of each component is comprehensively utilized to improve the overall efficiency of the thermochemical energy storage system and reduce energy loss.

[0027] The thermal conductivity of the thermochemical heat storage material obtained by the preparation method of the thermochemical heat storage material provided by the present invention can reach 1.099W / (m·K), which is increased by 43.5%.

[0028] The preparation method of the thermochemical heat storage material provided by the present invention is simple and has relatively low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Thermal conductivity diagram of thermochemical heat storage materials provided for Examples 1-5 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0030] The technical solution provided by the present invention is described in detail below by way of specific embodiments:

[0031] A thermochemical heat storage material, wherein the raw materials of the material include the following components in parts by mass: 50-99 parts of Ca(OH)2, 1-50 parts of a thermal conductivity enhancer, 1-6 parts of a surfactant, 1-3 parts of a thickener, and 4-6 parts of an emulsifier.

[0032] Through the above-mentioned proportion design, a thermochemical heat storage material with high heat storage density and good thermal conductivity can be prepared to meet the needs of efficient thermal energy storage and release. In the method for preparing the thermochemical heat storage material provided by the present invention, the ratio of Ca(OH)2 and thermal conductivity enhancer is (50-99): (1-50). As the proportion of thermal conductivity enhancer changes, the thermal conductivity of the thermochemical heat storage material shows an upward trend. By changing the mass ratio of Ca(OH)2 and thermal conductivity enhancer, linear adjustment of thermal conductivity can be achieved. Comprehensively utilize the synergistic effect of each component to improve the overall efficiency of the thermochemical energy storage system and reduce energy loss.

[0033] The particle size of Ca(OH)2 is 30-75 μm, and the particle size of the thermal conductivity enhancer is 0.1-60 μm.

[0034] A moderate particle size helps the heat storage material maintain a certain mechanical strength and structural stability, and also helps to increase the contact area between the thermal conductivity enhancer and Ca(OH)2, thereby more effectively improving the thermal conductivity of the overall composite material.

[0035] The thermal conductivity enhancer is at least one of graphite, silicon carbide, aluminum nitride, aluminum oxide and titanium oxide. Preferably, the thermal conductivity enhancer is selected from aluminum oxide with a particle size of 0.1 to 60 μm.

[0036] Alumina itself has a high thermal conductivity, especially in the particle size range of 0.1 to 60 μm, which can effectively improve the thermal conductivity of the composite material, and is also conducive to uniform dispersion in the matrix, reducing agglomeration, thereby more effectively forming a thermal network. Alumina has excellent thermal stability and can remain stable at high temperatures, which is particularly important for the application of thermochemical heat storage materials at high temperatures.

[0037] The surfactant is at least one of sodium dodecyl sulfate, hexadecyl trimethyl ammonium bromide, hexadecyl dimethyl ethyl ammonium bromide, hexadecyl trimethyl ammonium chloride and sodium polyoxyethylene fatty alcohol sulfate. Preferably, the surfactant is selected from sodium dodecyl sulfate.

[0038] Sodium dodecyl sulfate helps to improve the thermal conductivity of thermochemical heat storage materials, thereby improving the heat storage and release efficiency. In the process of preparing thermal conductivity enhanced thermochemical heat storage materials, sodium dodecyl sulfate is used to help mix Ca(OH)2 powder with other thermal conductivity enhancers. Sodium dodecyl sulfate helps to form a uniform precursor a, which promotes the formation of a uniform final product by improving the dispersibility of solid particles in the liquid medium.

[0039] The thickener is at least one of polyacrylamide and polyvinyl alcohol. Preferably, the thickener is selected from polyacrylamide.

[0040] Polyacrylamide helps to form a uniform precursor material a; it also helps to improve the stability of the final product under specific conditions; at the same time, it can control the reaction rate and optimize product performance.

[0041] The emulsifier is at least one of polyethylene glycol and propylene glycol. Preferably, the emulsifier is selected from polyethylene glycol.

[0042] Polyethylene glycol helps to form stable emulsions by reducing the attractive forces between droplets and preventing the separation of the different phases in the emulsion.

[0043] The preparation method of the thermochemical heat storage material comprises the following steps:

[0044] Mixing Ca(OH)2, a thermal conductivity enhancer, a surfactant, a thickener, and an emulsifier to obtain a first intermediate;

[0045] The first intermediate is dissolved in 35 to 50 parts of deionized water, and the second intermediate is obtained after stirring evenly. The stirring time is 1 to 3 hours. Appropriate stirring can prevent local overheating and ensure uniform temperature of the entire reaction system.

[0046] Deionized water acts as a solvent, allowing Ca(OH)2 and other solid components to be evenly dispersed and mixed. By adding an appropriate amount of deionized water, the viscosity of the mixture can be adjusted to facilitate handling and further processing. In some cases, deionized water can be used as a reaction medium to facilitate chemical reactions between components in the mixture.

[0047] The second intermediate is filtered and then vacuum dried. The vacuum drying temperature is controlled at 80-120°C for 11-13 hours. After drying, precursor a is obtained.

[0048] Filtration is used to separate solid particles from liquid media in a mixture, usually using filter media. Filtration can remove impurities and unwanted liquids from the mixture, thereby improving the purity and quality of the product. Filtration also helps remove water and other solvents adsorbed in the solid components, preparing for the next drying step.

[0049] The drying process helps control the morphology and structure of the solid components, thereby affecting their physical and chemical properties; at the same time, the dried solids make subsequent ball milling easier.

[0050] Precursor a and lubricant are placed in a planetary ball mill for ball milling. The ball milling time is 0.5 to 2 hours. After ball milling, the precursor b is calcined at high temperature. The molar ratio of Ca(OH)2 and lubricant is 1:0.5 to 1:5. The high-temperature calcination temperature is 500 to 1000°C and the time is 1 to 2 hours.

[0051] Ball milling can achieve uniform mixing of precursor a and lubricant at the molecular or nanometer level and improve the microstructure of the material; at the same time, the ball milling process can increase the surface activity of the material, which helps to achieve better physical and chemical changes in the subsequent calcination process.

[0052] The precursor b is placed in an inert gas atmosphere to fully react with water vapor to obtain a thermochemical heat storage material.

[0053] Water vapor treatment will form a structure in the material that is conducive to heat conduction, such as increasing crystallinity or forming a heat conduction channel. At the same time, water vapor treatment helps to improve the stability of the material in thermochemical reactions and ensure that its performance is maintained during long-term cyclic use.

[0054] The lubricant is selected from organic lubricants, and the organic lubricant is selected from ethanol.

[0055] Lubricants can reduce friction and wear between particles during ball milling and protect the surface of the material. Ethanol can also help absorb and disperse heat during ball milling to prevent the material from overheating.

[0056] When the first intermediate is stirred with deionized water, the temperature is controlled at 20-30° C., preferably, the stirring temperature is controlled at 25° C. Within this temperature range, some exothermic reactions or degradation reactions can be avoided from occurring too quickly, thereby controlling the reaction rate.

[0057] The inert gas includes at least one of nitrogen or argon.

[0058] Inert gases can prevent materials from reacting with oxygen during high temperature processing, avoid oxidation, and maintain the purity and performance of the materials. At the same time, during the heating process, inert gases provide a stable environment, reducing the possibility of combustion or exothermic reactions that may occur in certain materials.

[0059] Below is a combination of Examples 1 to 5, Comparative Examples 1 to 2 and Figure 1 The invention introduces a method for preparing a thermochemical heat storage material.

[0060] Figure 1 The dependent variable Thermal conductivity shown is the thermal conductivity value.

[0061] The thermal conductivity of the chemical heat storage materials of Examples 1 to 6 and Comparative Example 1 was tested using a laser thermal conductivity meter.

[0062] Test equipment: NETZSCH LFA457 laser thermal conductivity meter produced by NETZSCH, Germany.

[0063] Example 1

[0064] A thermochemical heat storage material, wherein the raw materials of the material include the following components in parts by mass: 83 parts of Ca(OH)2, 15 parts of a thermal conductivity enhancer, 3 parts of a surfactant, 3 parts of a thickener, and 5 parts of an emulsifier.

[0065] The method for preparing the above-mentioned thermochemical heat storage material comprises the following steps:

[0066] Add 83 parts of Ca(OH)2 with a particle size of 30 to 75 μm to 15 parts of alumina with a particle size of 0.1 to 60 μm, and then add 3 parts of sodium dodecyl sulfate, 3 parts of polyacrylamide, and 5 parts of polyethylene glycol, and mix well.

[0067] After mixing, 35 parts of deionized water were added, and the mixture was stirred at 20°C (stirring temperature) for 1 h (stirring time). After filtration, the mixture was placed in a vacuum drying oven at 80°C (drying temperature) for 11 h (drying time) to obtain a solid powder.

[0068] The obtained solid powder and ethanol are placed in a planetary ball mill with a molar ratio of Ca(OH)2 to ethanol of 1:0.5; under air atmosphere (the ball mill is an agate ball mill and the abrasive material is agate), the ball mill is performed at a main disk speed of 300RPM and a grinding jar speed of 900RPM for 0.5h (ball milling time).

[0069] After ball milling, the resulting mixture was placed in a muffle furnace and calcined at 500° C. (calcination temperature) for 1 h (calcination time) to obtain precursor b.

[0070] The obtained precursor b was placed in a circulation test furnace and fully reacted with water vapor for 1 hour at 120° C. in a nitrogen atmosphere to obtain the thermochemical heat storage material.

[0071] Embodiment 2-5

[0072] The thermochemical energy storage materials provided in Examples 2-5 have raw material contents as shown in Table 1:

[0073] Table 1 Summary of raw materials in the examples

[0074]

[0075] The preparation method of the thermochemical heat storage material provided in Examples 2-5 is the same as that in Example 1, except that the preparation conditions are different, as shown in Table 2:

[0076] Table 2 Summary of preparation conditions of the examples

[0077]

[0078] Comparative Example 1

[0079] A thermochemical heat storage material, wherein the raw materials of the material include the following components in parts by mass: 70 parts of Ca(OH)2, 3 parts of a surfactant, 3 parts of a thickener, and 5 parts of an emulsifier.

[0080] The method for preparing the above-mentioned thermochemical heat storage material comprises the following steps:

[0081] Add 70 parts of Ca(OH)2 with a particle size of 30 to 75 μm to 3 parts of sodium dodecyl sulfate, 3 parts of polyacrylamide and 5 parts of polyethylene glycol by mass and mix well.

[0082] After mixing, add 40 parts of deionized water, stir thoroughly at 20°C for 1 hour, filter, and dry in a vacuum drying oven at 80°C for 11 hours to obtain a solid powder;

[0083] The obtained solid powder and ethanol were placed in a planetary ball mill with a molar ratio of Ca(OH)2 to ethanol of 1:5; the ball mill was performed for 0.5 h at a main plate speed of 300 RPM and a grinding jar speed of 900 RPM under air atmosphere (the ball mill was an agate ball mill and the abrasive material was agate);

[0084] After ball milling, the resulting mixture was placed in a muffle furnace and calcined at 500° C. for 1 h to obtain precursor b.

[0085] The obtained precursor b was placed in a circulation test furnace, and fully reacted with water vapor for 1 hour at 120° C. in an argon atmosphere to obtain the thermochemical heat storage material.

[0086] Comparative Example 2

[0087] A thermochemical heat storage material, wherein the raw materials of the material include the following components in parts by mass: 25 parts of Ca(OH)2, 1 part of a thermal conductivity enhancer, 1 part of a surfactant, 1 part of a thickener, and 4 parts of an emulsifier.

[0088] The method for preparing the above-mentioned thermochemical heat storage material comprises the following steps:

[0089] Add 25 parts of Ca(OH)2 with a particle size of 30 to 75 μm to 1 part of graphite powder, and then add 1 part of sodium dodecyl sulfate, 1 part of polyacrylamide, and 4 parts of polyethylene glycol, and mix well.

[0090] After mixing, add 35 parts of deionized water, stir thoroughly at 30°C for 3 hours, filter, and dry in a vacuum drying oven at 120°C for 13 hours to obtain a solid powder;

[0091] The obtained solid powder and ethanol were placed in a planetary ball mill with a molar ratio of Ca(OH)2 to ethanol of 1:1; the ball mill was performed for 2 h at a main plate speed of 300 RPM and a grinding jar speed of 900 RPM under air atmosphere (the ball mill was an agate ball mill and the abrasive material was agate);

[0092] After ball milling, the obtained mixture was placed in a muffle furnace and calcined at 1000°C for 2 h to obtain precursor b.

[0093] The obtained precursor b was placed in a circulation test furnace, and fully reacted with water vapor for 1 hour at 120° C. in a nitrogen atmosphere to obtain the thermochemical heat storage material.

[0094] Comparison test

[0095] The thermochemical energy storage materials obtained in Examples 1-5 and Comparative Examples 1-2 were respectively pressed into samples with a diameter of about 12.70 mm and a thickness of 1 to 2 mm using a tablet press, and graphite coating was sprayed on both sides. After the coating was naturally air-dried, the sample was placed in an alumina crucible with a diameter of 12.70 mm. The temperature control program was heated from room temperature to 300°C, and the heating and cooling rates were both 10K / min. The argon flow rate was 50ml / min. After the temperature reached 300°C and stabilized, the thermal conductivity of the material was tested. The test results are shown in Table 3 below.

[0096] Table 3 Comparison of thermal conductivity

[0097]

[0098]

[0099] Compared with Comparative Example 1, the thermal conductivity of the thermochemical heat storage material obtained by the method provided in Example 1 of the present invention is increased by 14.88%, the thermal conductivity of the thermochemical heat storage material obtained by the method provided in Example 2 of the present invention is increased by 26.24%, the thermal conductivity of the thermochemical heat storage material obtained by the method provided in Example 3 of the present invention is increased by 30.94%, the thermal conductivity of the thermochemical heat storage material obtained by the method provided in Example 4 of the present invention is increased by 39.95%, and the thermal conductivity of the thermochemical heat storage material obtained by the method provided in Example 5 of the present invention is increased by 43.47%.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents, and any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A thermochemical heat storage material, characterized in that: include: The raw materials of the material include the following components in parts by mass: 50-99 parts of Ca(OH)2, 1-50 parts of thermal conductivity enhancer, 1-6 parts of surfactant, 1-3 parts of thickener, and 4-6 parts of emulsifier.

2. A thermochemical heat storage material according to claim 1, characterized in that: The Ca(OH)2 particle size is 30 to 75 μm.

3. A thermochemical heat storage material according to claim 1, characterized in that: The particle size of the thermal conductivity enhancer is 0.1 to 60 μm.

4. A thermochemical heat storage material according to claim 3, characterized in that: The thermal conductivity enhancer is at least one of graphite, silicon carbide, aluminum nitride, aluminum oxide and titanium oxide.

5. A thermochemical heat storage material according to claim 1, characterized in that: The surfactant is at least one of sodium dodecyl sulfate, hexadecyl trimethyl ammonium bromide, hexadecyl dimethyl ethyl ammonium bromide, hexadecyl trimethyl ammonium chloride and sodium polyoxyethylene fatty alcohol sulfate.

6. A thermochemical heat storage material according to claim 1, characterized in that: The thickener is at least one of polyacrylamide and polyvinyl alcohol.

7. A thermochemical heat storage material according to claim 1, characterized in that: The emulsifier is at least one of polyethylene glycol and propylene glycol.

8. A method for preparing a thermochemical heat storage material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing Ca(OH)2, a thermal conductivity enhancer, a surfactant, a thickener, and an emulsifier to obtain a first intermediate; Dissolving the first intermediate in 35 to 50 parts of deionized water and stirring evenly to obtain a second intermediate; The second intermediate is filtered and then vacuum dried to obtain precursor a; The precursor a and the lubricant are placed in a planetary ball mill for ball milling and then calcined at high temperature to obtain the precursor b; The precursor b is placed in an inert gas atmosphere to fully react with water vapor to obtain the thermochemical heat storage material.

9. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The lubricant is selected from organic lubricants, and the organic lubricant is selected from ethanol.

10. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: When the first intermediate is stirred with deionized water, the stirring temperature is 20-30° C. and the stirring time is 1-3 hours.

11. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The molar ratio of Ca(OH)2 to lubricant is 1:0.5 to 1:

5.

12. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The inert gas includes at least one of nitrogen or argon.

13. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The vacuum drying has a drying temperature of 80 to 120° C. and a drying time of 11 to 13 hours.

14. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The ball milling time is 0.5 to 2 hours.

15. The method for preparing a thermochemical heat storage material according to claim 8, characterized in that: The calcination temperature during the high-temperature calcination is 500-1000° C., and the calcination time is 1-2 hours.